UJI SENSITIVITAS DAN SPESIFISITAS TROPONIN I DAN TROPONIN T SEBAGAI PENANDA BIOKIMIA JANTUNG UNTUK MENEGAKKAN DIAGNOSIS ACUTE MYOCARDIAL INFARCTION (AMI) - Friska O; Tristina N; Suraya N (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2008)
Acute coronary syndrome (ACS) is the most common heart disease and has been a leading cause of mortality in Indonesia’s and developed countries population aged over 45 years endemic. The diagnosis of ACS is made by fulfilling 2 of 3 WHO criteria: typicalishemic chest pain, electrocardiogram (ECG) changes specific for ACS and the raise of cardiac biochemical markers. Cardiac troponin T(cTnT) or I (cTnI) are two novel biomarkers with high diagnostic sensitivity and specificity for early diagnosis of ACS especially acutemyocardial infarction (AMI). Troponin I and T are proteins of cardiac myofibrils, released into the bloodstream in the death damages ofcardiomyocyte caused by AMI or injury.The level of cTnI will not increased in patients with decreased renal functions, which is distinctfrom cTnT. The aims of study are to define the sensitivity and specificity of cTnI and cTnT to be cardiac biochemical markers for AMIpatients. From 41 subjects; 29 AMI and 12 subjects non AMI patients in Cardiac Intensive Care Units (CICU) and Emergency Room(ER) of Rumah Sakit Dr. Hasan Sadikin (RSHS) Bandung from September to October 2007 was evaluated. Design of the study was cross sectional and quantitative observational study. The cTnI and cTnT assay using the quantitative immunochromatography method.Sensitivity, spesificity, Positive Predictive Value (PPV) and Negative Predictive Value (NPV) in subjects who met 2 WHO criteria for AMI,Troponin I was 74%, 86%, 96% and 40%. Sensitivity, spesificity, PPV and NPV In subjects who met 3 WHO criteria for AMI, Troponin Iwas 89%, 57%, 62% and 87%. Sensitivity, specificity, PPV and NPV cTnI was 90%, 100% 100 and 80% for diagnosis of AMI. In subjectswho met 2 WHO criteria for AMI, Troponin T Sensitivity, specificity, PPV and NPV has 88%, 71%, 94% and 56%. In subjects who met3 WHO criteria for AMI sensitivity, specificity, PPV and NPV Troponin T was 94%, 35%, 53% and 89%. And Sensitivity, specificity, PPVand NPV Troponin T was 97%, 67%, 88%, and 89% for diagnosis of AMI. Troponin T is more sensitive than troponin I, but troponin Ihas greater specificity than troponin T in AMI. Troponin I is more specific because no influence from renal dysfunction.